2016
DOI: 10.1016/j.neuropharm.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the lateral orbitofrontal cortex increases drinking in ethanol-dependent but not non-dependent mice

Abstract: Long-term consumption of ethanol affects cortical areas that are important for learning and memory, cognition, and decision-making. Deficits in cortical function may contribute to alcohol-abuse disorders by impeding an individual’s ability to control drinking. Previous studies from this laboratory show that acute ethanol reduces activity of lateral orbitofrontal cortex (LOFC) neurons while chronic exposure impairs LOFC-dependent reversal learning and induces changes in LOFC excitability. Despite these findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Interestingly, studies with rats have reported an increase in alcohol intake over time in the 2‐bottle choice 24‐hour intermittent access paradigm (Bito‐Onon, Simms et al, ; Mill, Bito‐Onon et al, ; Simms, Steensland et al, ). However, this phenomenon is less consistent in mice with increases being reported in some studies (Hwa, Nathanson et al, ; Melendez, ), but not others (Crabbe, Harkness et al, ) including previous studies from our laboratory (den Hartog, Beckley et al, , den Hartog, Zamudio‐Bulcock et al, ). Together, these findings suggest that EtOH‐sensitive GluN2A‐containing NMDARs are not critical for regulating voluntary alcohol consumption in non‐dependent animals.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, studies with rats have reported an increase in alcohol intake over time in the 2‐bottle choice 24‐hour intermittent access paradigm (Bito‐Onon, Simms et al, ; Mill, Bito‐Onon et al, ; Simms, Steensland et al, ). However, this phenomenon is less consistent in mice with increases being reported in some studies (Hwa, Nathanson et al, ; Melendez, ), but not others (Crabbe, Harkness et al, ) including previous studies from our laboratory (den Hartog, Beckley et al, , den Hartog, Zamudio‐Bulcock et al, ). Together, these findings suggest that EtOH‐sensitive GluN2A‐containing NMDARs are not critical for regulating voluntary alcohol consumption in non‐dependent animals.…”
Section: Discussionmentioning
confidence: 56%
“…Outside of reinstatement, at least 2 other studies have found an impact of OFC manipulation on motivation for EtOH. In these studies, however, lesions or DREADD inhibition of OFC increased drinking in rats (Ray et al, 2018) and mice treated with chronic EtOH (den Hartog et al, 2016). In the study by den Hartog and colleagues, mice with OFC lesions increased EtOH consumption after, but not before, chronic intermittent EtOH (CIE) vapor treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Inhibition of OFC reduces cue-and context-induced reinstatement of alcohol seeking (Arinze and Moorman, 2020;Bianchi et al, 2018), and disruption of mTORC1 signaling in OFC decreased alcohol seeking during extinction (Morisot et al, 2019). In other studies, however, lesions or DREADD (designer receptor exclusively activated by designer drugs; (Armbruster et al, 2007)) inhibition of OFC increased drinking in rats (Ray et al, 2018) and mice treated with chronic ethanol (EtOH;den Hartog et al, 2016). Despite some conflicting results, these data indicate a clear involvement of OFC in alcohol seeking.…”
mentioning
confidence: 91%
“…Alcohol vapor exposure also induces an increase in excitability, synaptic plasticity and spine density in lateral OFC neurons that may contribute to the OFC-dependent behavioral-deficits (McGuier et al, 2015). A recent study showed that inactivation of the lateral OFC by excitotoxic lesion or in response to the activation of inhibitory DREADD (designer receptor exclusively activated by designer drug) reduced alcohol drinking in mice previously exposed to vapor, revealing a role for the OFC in alcohol-related behaviors (Hartog et al, 2016). In addition, we previously found that a short period of reconsolidation of alcohol memories resulted in mTORC1 activation in the OFC (but not in the NAc) of rats, and that systemic administration of rapamycin following reactivation of alcohol memories disrupted reconsolidation leading to reduction in alcohol seeking on the following day (Barak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%